Administration of multipotent mesenchymal stromal cells restores liver regeneration and improves liver function in obese mice with hepatic steatosis after partial hepatectomy. Issue 1 (December 2017) - Ezquer, Fernando; Bahamonde, Javiera; Huang, Ya-Lin; Ezquer, Marcelo
Abstract Background The liver has the remarkable capacity to regenerate in order to compensate for lost or damaged hepatic tissue. However, pre-existing pathological abnormalities, such as hepatic steatosis (HS), inhibits the endogenous regenerative process, becoming an obstacle for liver surgery and living donor transplantation. Recent evidence indicates that multipotent mesenchymal stromal cells (MSCs) administration can improve hepatic function and increase the potential for liver regeneration in patients with liver damage. Since HS is the most common form of chronic hepatic illness, in this study we evaluated the role of MSCs in liver regeneration in an animal model of severe HS with impaired liver regeneration. Methods C57BL/6 mice were fed with a regular diet (normal mice) or with a high-fat diet (obese mice) to induce HS. After 30 weeks of diet exposure, 70% hepatectomy (Hpx) was performed and normal and obese mice were divided into two groups that received 5 × 105 MSCs or vehicle via the tail vein immediately after Hpx. Results We confirmed a significant inhibition of hepatic regeneration when liver steatosis was present, while the hepatic regenerative response was promoted by infusion of MSCs. Specifically, MSC administration improved the hepatocyte proliferative response, PCNA-labeling index, DNA synthesis, liver function, and also reduced the number of apoptotic hepatocytes. These effects may be associated to the paracrine secretion of trophic factors by MSCs and the hepatic upregulation of key cytokines and growth factors relevant for cell proliferation, which ultimately improves the survival rate of the mice. Conclusions MSCs represent a promising therapeutic strategy to improve liver regeneration in patients with HS as well as for increasing the number of donor organs available for transplantation.